Karakter Hukum Perusahaan Perseroan dan Status Hukum Kekayaan yang Dimilikinya - Ridwan Khairandy (Fakultas Hukum Universitas Islam Indonesia, 2013)
The legal status of Persero assets causes different interpretation of the definition of state finance in several regulations of law. This research studies: First, legal characters of Persero; second, legal status of Persero assets. This research is normative research referring to legal principles and norms stipulated in the regulations of law. The instruments used to collect the legal materials were literature and document studies. This research concludes that first, Persero is identical with Limited Liability Company. Persero is not public legal entity but private legal entity subject to private law. Second, all assets of a Persero belong to the Persero instead of state. State asset in the Persero is the shares owned.